Mechanical and physical properties of carbon black filled elastomer (NR and ePDM) / Syazrie Adley Nor Azman - Nor Azman, Syazrie Adley (2000)
Carbon black is well known as a filler in producing synthetic rubber compounding. Ethylene-propylene-diene terporymers (EPDM) are extensively used in many latest and present innovative creation such as wire and cable, automotive radiator hose, white sidewalls of tires and many other specialty applications due to their excellent resistance to oxygen, ozone, heat and ionization effects, as well as for their unusual ability to accept high loadings of fillers and oils. The main objective of this experiment is to study and compare the physical and mechanical properties of ethylene propylene-diene terpolymer (EPDM) filled with carbon black and Natural Rubber (NR) filled with carbon black. Various percentages compounding of carbon black with rubber (NR and EPDM) and to study the curing characteristic of compounded material. In this study also gives the on-hand experience on handling machine that is available in most of the polymer industries in Malaysia.